Development of a core outcome set for cutaneous squamous cell carcinoma trials: identification of core domains and outcomes*. (1st June 2021) - Reynolds, K.A.; Schlessinger, D.I.; Yanes, A.F.; Godinez‐Puig, V.; Chen, B.R.; Kurta, A.O.; Cotseones, J.K.; Chiren, S.G.; Iyengar, S.; Ibrahim, S.A.; Kang, B.Y.; Worley, B.; et al.
Summary: Background: The lack of uniformity in the outcomes reported in clinical studies of the treatment of cutaneous squamous cell carcinoma (cSCC) complicates efforts to compare treatment effectiveness across trials. Objectives: To develop a core outcome set (COS), a minimum set of agreed‐upon outcomes to be measured in all clinical trials of a given disease or outcome, for the treatment of cSCC. Methods: One hundred and nine outcomes were identified via a systematic literature review and interviews with 28 stakeholders. After consolidation of this long list, 55 candidate outcomes were rated by 19 physician and 10 patient stakeholders, in two rounds of Delphi exercises. Outcomes scored 'critically important' (score of 7, 8 or 9) by ≥ 70% of patients and ≥ 70% of physicians were provisionally included. At the consensus meeting, after discussion and voting of 44 international experts and patients, the provisional list was reduced to a final core set, for which consensus was achieved among all meeting participants. Results: A core set of seven outcomes was finalized at the consensus meeting: (i) serious or persistent adverse events, (ii) patient‐reported quality of life, (iii) complete response, (iv) partial response, (v) recurrence‐free survival, (vi) progression‐free survival and (vii) disease‐specific survival. Conclusions: In order to increase the comparability of results across trials and to reduce selective reporting bias, cSCC researchers should consider reporting these core outcomes. Further work needs to be performed to identify the measures that should be reported for each of these outcomes. Abstract: What is already known about this topic? Although many outcomes have been measured in studies of cutaneous squamous cell carcinoma (cSCC), lack of a standardized set of such outcomes is an obstacle to the synthesis of evidence across trials. What does this study add? This study reports the development of a core outcome set for treatment of cSCC based on a systematic literature search, stakeholder interviews, and an international e‐Delphi consensus process among patients and physicians. The minimum set of outcomes to be reported in clinical trials of cSCC comprises (i) serious or persistent adverse events, (ii) patient‐reported quality of life, (iii) complete response, (iv) partial response, (v) recurrence‐free survival, (vi) progression‐free survival and (vii) disease‐specific survival. What are the clinical implications of this work? Adoption of this core outcome set by investigators is likely to reduce selective reporting bias, facilitate systematic reviews and meta‐analyses, permit refinement of treatment guidelines, and ultimately improve patient outcomes.